UNIVERSITY STUDENTS’ NEEDS OF WRITING COURSE MATERIALS: A CASE OF INDONESIA - Ilham Ilham; Bachrudin Musthafa; Fazri Nur Yusuf (English Review: Journal of English Education, 2020)
The aim of this study is to explore the target needs (i.e. necessities, lacks and wants) of the students to inform academic writing courses materials. A case study design was employed as this design to provide in-depth data information. To collect the data, questionnaire and interviews were used. Twenty-three undergraduate students of English department at a private university in Mataram West Nusa Tenggara who take academic writing course in the 2019-2020 academic year participated in the study. The result of the study showed that the students need to learn the types of writing texts, vocabulary and construct sentences into paragraph, have good skills in writing different genres since they are lack of grammar knowledge and vocabularies, and improvement on the aspect of teaching writing. This finding may promise implications for updating the current curriculum and materials as practiced for tertiary level English department students in an attempt to keep up with the latest changes in the methodologies of English language teaching. This study recommends that lecturers and universities should conduct a need analysis regularly and updated the curriculum with such insightful needs.